2011
DOI: 10.3171/2010.10.spine10189
|View full text |Cite
|
Sign up to set email alerts
|

Survival of patients with malignant primary osseous spinal neoplasms: results from the Surveillance, Epidemiology, and End Results (SEER) database from 1973 to 2003

Abstract: Object Malignant primary osseous spinal neoplasms are aggressive tumors that remain associated with poor outcomes despite aggressive multidisciplinary treatment measures. To date, prognosis for patients with these tumors is based on results from small single-center patient series and controlled trials. Large population-based observational studies are lacking. To assess national trends in histology-specific survival, the authors reviewed patient survival data spanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
93
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(107 citation statements)
references
References 42 publications
(35 reference statements)
9
93
2
3
Order By: Relevance
“…According to the results of large scale population registries, the incidence of primary sacral tumors varies between 32% and 71% of all primary spinal tumors 10,11 . The most common primary malignant tumors of the sacrum are chordoma and sacral sarcomas like chondrosarcoma, osteosarcoma and Ewing sarcoma 12 .…”
Section: Epidemiology Of Primary Malignant Sacral Tumorsmentioning
confidence: 99%
“…According to the results of large scale population registries, the incidence of primary sacral tumors varies between 32% and 71% of all primary spinal tumors 10,11 . The most common primary malignant tumors of the sacrum are chordoma and sacral sarcomas like chondrosarcoma, osteosarcoma and Ewing sarcoma 12 .…”
Section: Epidemiology Of Primary Malignant Sacral Tumorsmentioning
confidence: 99%
“…Its ability to halt growth of tumor has been described. [72][73][74] Lackman et al 58 reported on 5 cases of sacral GCT treated solely with recurrent arterial embolization, with 4 demonstrating no growth or recurrence. Intralesional curettage is the mainstay of treatment in long bones and is often combined with local adjuvants such as cryotherapy, peroxide, ethanol, phenol, and bone cement to reduce recurrence.…”
Section: Surgical Pearlsmentioning
confidence: 99%
“…1,13,14,16,17,26,27,30,31,38,63,93,[95][96][97][98] However, surgical approaches to spinal tumors often necessitate extensive reconstruction of the spinal column and may require adjuvant chemotherapy or radiation; therefore, perioperative complication rates after spinal tumor surgery are higher than in other spinal operations. [34][35][36][46][47][48]50,52,65,67,68,78,80,81,[86][87][88]95,100 It is especially important to understand the incidence and predictive factors for adverse events in spinal oncology patients, as a single complication may be associated with morbidity, mortality, and costs. 1,31,37,46,47,52,62,70,72,79,86,95 Risk stratification of patients preoperatively is important to optimize outcomes, …”
mentioning
confidence: 99%